BeiDou-3 orbit and clock quality of the IGS Multi-GNSS Pilot Project. Issue 1 (1st January 2023) - Steigenberger, Peter; Deng, Zhiguo; Guo, Jing; Prange, Lars; Song, Shuli; Montenbruck, Oliver
Highlights: Five IGS analysis centers provide BeiDou-3 orbit and clock products. BeiDou-3 MEO satellite orbits have a consistency of 4–8 cm. PPP with BeiDou-3 MGEX products gives a precision of 7–8 mm. Abstract: Within the Multi-GNSS Pilot Project (MGEX) of the International GNSS Service (IGS), precise orbit and clock products for the BeiDou-3 global navigation satellite system (BDS-3) are routinely generated by a total of five analysis centers. The processing standards and specific properties of the individual products are reviewed and the BDS-3 orbit and clock product performance is assessed through direct inter-comparison, satellite laser ranging (SLR) residuals, clock stability analysis, and precise point positioning solutions. The orbit consistency evaluated by the signal-in-space range error is on the level of 4–8 cm for the medium Earth orbit satellites whereas SLR residuals have RMS values between 3 and 9 cm. The clock analysis reveals sytematic effects related to the elevation of the Sun above the orbital plane for all ACs pointing to deficiencies in solar radiation pressure modeling. Nevertheless, precise point positioning with the BDS-3 MGEX orbit and clock products results in 3D RMS values between 7 and 8 mm.